S.B. 9: A Second Chance for Juveniles Serving Life without Parole in California in Theory - and Why It Won't Make a Difference in Practice - Reese, Evan (2014)
Historically, juveniles have been treated differently than adults when convicted of a crime. They were seen as less culpable than adults and more capable of reform. In California and in many other states, however, some juveniles have been tried as adults in a variety of situations. Recent legislation in California has offered a glimmer of hope, and perhaps a second chance, for some juvenile offenders who have been sentenced as adults to life without parole. S.B. 9 allows such juveniles to petition the court for resentencing after serving the first fifteen years of their life sentence. In theory, if the prisoner is successful, he would serve a reduced sentence-most likely twenty-five years to life. In practice, however, the Bill is unlikely to have any significant practical effect on the hundreds of prisoners it aims to help. This Note argues that S.B. 9 will likely have little practical effect for juveniles sentenced to life without parole. Instead, to remedy the current injustices, protect future victims, and to fix the unconstitutional overcrowding in prisons, California should outlaw life without parole as a potential punishment for crimes committed as a juvenile, and retroactively resentence all those currently serving such terms